2019
DOI: 10.3390/en12173386
|View full text |Cite
|
Sign up to set email alerts
|

Study on Riblet Drag Reduction Considering the Effect of Sweep Angle

Abstract: This study computationally evaluates the riblet drag reduction effect considering the effect of sweep angle. An implicit large eddy simulation is performed on a channel flow and an infinite swept wing. First, three different inclined angles between the riblets and the flow direction are tested in the channel flow. The results show that with increases in the inclined angle, the friction drag decreases, while the pressure drag increases approximately quadratically. The riblets with a 30° inclined angle increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The effect of crossflows on the ribbed surfaces has been investigated in a number of studies [26,53,70,74,131]. Supercritical airfoils and swept wings are commonly employed in commercial aircraft to enhance stability and enable high-speed flights.…”
Section: Crossflows and Riblet Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of crossflows on the ribbed surfaces has been investigated in a number of studies [26,53,70,74,131]. Supercritical airfoils and swept wings are commonly employed in commercial aircraft to enhance stability and enable high-speed flights.…”
Section: Crossflows and Riblet Surfacesmentioning
confidence: 99%
“…The optimum design of riblet geometries, in terms of direction, configuration, height and spacing, should consider the flow behavior over the solid surfaces. Infinite wings were investigated by considering the effect of yaw angle [53,131]. Sundaram et al [53] carried out experimental studies with a 25 • yaw angle.…”
Section: Crossflows and Riblet Surfacesmentioning
confidence: 99%
“…The drag increased when the yaw angle was 20 • or higher (Hirschel et al 1989, Enyutin et al 1991. A study using numerical simulations of blade riblets in channel flow also reported that the total drag with a yaw angle of 30 • was larger than that without riblets, where the friction drag decreased but the pressure drag increased (Zhang and Yin 2019).…”
Section: Introductionmentioning
confidence: 96%
“…Studies have shown that the drag reduction ability of Blade surfaces is sensitive to the yaw angle, which is the angle between the design direction of the riblet surface and the average flow direction. ,, The average flow direction rarely aligns with the designed direction of a riblet surface in various practical applications, such as side wind, vehicle steering, and swept wing aircraft while climbing . Studies have shown that the drag reduction ability of Blade surfaces decreases sharply as the yaw angle increases. ,,, When the flow direction is deflected, the interactions between structural surfaces and wall-bounded turbulence are subject to the combined effects of streamwise and spanwise directions rather than the effects of a single direction . Considering the spanwise influences of near-wall flow fields, previous studies have investigated Wavy, Sinusoidal, and Herringbone surfaces, which were designed to be parallel to the average flow direction.…”
Section: Introductionmentioning
confidence: 99%
“…22 Studies have shown that the drag reduction ability of Blade surfaces decreases sharply as the yaw angle increases. 18,20,21,23 When the flow direction is deflected, the interactions between structural surfaces and wallbounded turbulence are subject to the combined effects of streamwise and spanwise directions rather than the effects of a single direction. 24 Considering the spanwise influences of nearwall flow fields, previous studies have investigated Wavy, Sinusoidal, and Herringbone surfaces, which were designed to be parallel to the average flow direction.…”
Section: Introductionmentioning
confidence: 99%